Canadian Vision Standards - Hovis, J.K (Canadian Journal of Optometry, 2021)
As primary vision care providers, optometrists are often asked whether a patient's vision meets the standard established for a particular occupation. In order to address these inquiries appropriately, optometrists must have knowledge of the various vision standards. This article provides a summary of federally-mandated vision requirements as a reference. However, because these standards are under continual revision, it will be necessary to update them from time to time.